Super-light Cu@Ni nanowires/graphene oxide composites for significantly enhanced microwave absorption performance - Xiaoxia Wang (Nature Portfolio, 2017)
Abstract Graphene oxide (GO) was rarely used as microwave absorption (MA) material due to its lower dielectric loss compared with reduced GO (RGO). However, the characteristics of low conductivity, light weight, and large surface area were beneficial to the impedance matching for absorbers already containing highly conductive metal materials. Cu@Ni nanowires are promising MA materials due to the desired dielectric loss from copper and excellent magnetic loss from nickel. However, the high density was an impediment to its further application. Combining Cu@Ni nanowires with GO should be an effective solution to decrease the absorber’s density and improve its MA properties. Herein, we demonstrated that Cu@Ni nanowires/GO composites exhibited enhanced MA capacities compared with Cu@Ni nanowires or GO alone, and the minimum reflection loss reached −42.8 dB at 16.9 GHz with a thickness of 2.1 mm. The enhanced MA performance mainly originated from good impedance matching, as a result of the addition of low conductivity of GO. To confirm this point, the MA performance of Cu@Ni nanowires/RGO was studied, and unsurprisingly, weak MA performance was obtained. Our work provides a new strategy to decrease the density, broaden the frequency band and tune MA performance of composites.